Analysis of the effects of the first phase of COVID-19 pandemic on mobility choices in Italy by a multi-criteria approach - Campisi, Tiziana; Moslem, Sarbast; Duleba, Szabolcs; Tanbay, Nurten Akgün; Szmelter–Jarosz, Agnieszka; Tesoriere, Giovanni (Palacky University Olomouc, 2022)
COVID-19 pandemic has caused changes in logistics and mobility. Concerning Italian road mobility, between March and April 2020, there has been a reduction in traffic for both light vehicles and heavy goods vehicles. Italy was the first European country to implement a total lockdown, starting on March 9th, causing a deep contraction in road traffic. This paper explores the main differences in mobility choices before and after the COVID-19 pandemic in 2020. A multi-criteria decision-making method was selected for the analysis of questionnaire survey data. The fuzzy Analytic Hierarchy Process was applied, considering eight mobility types: bus, tram, taxi, train, shared vehicles, multiple modes, walking and car. An evaluation process was adopted for the modal mobility choices of the residents of Sicily, Italy. The results show a significant decline in mobility demand during the first phase of the pandemic, especially in public transport mode. The findings provide a deeper understanding of the need to implement strategies to respect the constraints generated by the pandemic and revive the penalised transport and mobility-related sectors. Furthermore, the study’s findings provide valuable insights for the policymakers, both national and local, about the mobility results of the lockdown and can be used as a forecast benchmark for planning the restrictions in the future, in case of another unexpected phenomenon, e.g., pandemic. © 2022 The Author(s).
Keywords: Analytic Hierarchy Process; COVID-19; Fuzzy set; Mobility patterns; Sustainable mobility